Mean platelet volume and macrovascular complications in type 2 diabetes mellitus - Hanan Mohammed Amr; Khaled Mahmoud Makboul; Basem murad Mostafa; Yasmin Abd El majeed Mohammed; Caroline Adel Girgis Bishay (The Egyptian Journal of Internal Medicine)
Abstract Background Type 2 diabetes mellitus (T2DM) and its associated atherosclerosis are increasing globally. Platelets play a crucial role in the development of atherosclerosis. There are suggestions that a larger mean platelet volume (MPV), increases the risk of atherosclerosis. Objective We studied the relationship between MPV and macrovascular complications in T2DM. Methods We conducted the study on 150 subjects aged 40–60 years categorised into four groups. Group 1 included 30 T2DM patients without a history of macrovascular complications. Group 2 comprised 60 T2DM patients experiencing a macrovascular complication for the first time with 30 having cerebrovascular stroke and 30 having myocardial infarction. Group 3 consisted of 30 non-diabetic patients experiencing macrovascular complications for the first time with 15 having cerebrovascular stroke and 15 having myocardial infarction. Group 4 included 30 healthy non-diabetic subjects. We measured MPV and carotid intima-media thickness for all participants. Results Comparing the four groups we found a significant difference in MPV and carotid intima-media thickness. Post hoc analysis demonstrated that these were significantly higher in T2DM patients with macrovascular complications than in other groups. A Receiver operating characteristic curve determined a MPV threshold of 11.5 fl to discriminate between T2DM patients with and without macrovascular complications, with a sensitivity of 86.67%, specificity 73.33% and an AUC 0.761. In all participants, MPV positively correlated with glycaemic markers and the intima-media thickness. Conclusion MPV is linked to macrovascular complications in T2DM. MPV could be simple and cost-effective predictor of cerebrovascular stroke and myocardial infarction in diabetes mellitus.